Learning and video games - Leticia Staub Limberger; César Augusto Müller; Maira Meira Pinto (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
This research uses the complexity paradigm to discuss videogames as technical objects; open relational spaces, dialogic and unpredictable. Its unpredictability allows us to explore the human dimensions regarding the structural coupling and the Autopoiesis, essential concepts to understand learning through videogames. The research presented here has as methodological approach the cartographic method, which belongs to the present, and refers to a process that is happening, an action that is being developed to meet a reality. The reality we seek to set / know is that of a group of teenagers from Santa Cruz do Sul and its relation to videogames. The text is narrative as a way to give embodiment to the experience which is produced by the group.